2010
DOI: 10.1111/j.1538-7836.2010.03931.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of canine coagulation factor VII and its complex formation with tissue factor: canine–human cross‐species compatibility

Abstract: To cite this article: Knudsen T, Kristensen AT, Sørensen BB, Olsen OH, Stennicke HR, Petersen LC. Characterization of canine coagulation factor VII and its complex formation with tissue factor: canine-human cross-species compatibility. J Thromb Haemost 2010; 8: 1763-72.Summary. Background: Canine models have been good predictors of efficacy of hemophilia treatments, including recombinant human coagulation factor (F)VIIa (hFVIIa). However, canine FVIIa and tissue factor (TF) have remained incompletely character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 60 publications
1
22
1
Order By: Relevance
“…Human FVII can form a functional extrinsic tenase with canine TF, with canine and human TF working equally well to initiate coagulation in human plasma. 32 In the present study, canine cells triggered thrombin generation in canine and human plasma; however, there were notable differences. There was a longer lag time and larger amounts of thrombin were generated in factor-replete human versus canine plasma.…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…Human FVII can form a functional extrinsic tenase with canine TF, with canine and human TF working equally well to initiate coagulation in human plasma. 32 In the present study, canine cells triggered thrombin generation in canine and human plasma; however, there were notable differences. There was a longer lag time and larger amounts of thrombin were generated in factor-replete human versus canine plasma.…”
Section: Discussioncontrasting
confidence: 51%
“…Commercially available human plasma was used because specific factor-deficient canine plasma and inhibitory antibodies against canine coagulation factors were unavailable, and it has been shown that canine TF can efficiently bind to and act as a cofactor for canine and human FVII. 32 Plasma was stored in single-use aliquots at −80°C and thawed to 37°C before use, and samples were depleted of microparticles before use in CAT by centrifugation at 13,523 × g for 20 minutes, twice, at 4°C.…”
Section: Methodsmentioning
confidence: 99%
“…42 Binding of canine clotting factors to human tissue factor has been demonstrated to be decreased compared to the binding of human clotting factors to human tissue factor, the interaction from which thromboplastin sensitivity and the ISI are in part derived. 42,43 To the authors' knowledge, there is no data currently available on thromboplastin sensitivity to canine clotting factors or on an ISI specific for canine samples. It has been demonstrated that correcting PT clotting data by the INR may not produce equivalent results when clotting times are measured using different thromboplastin reagents, 42 so it is unclear to what degree the INR values were affected in the patients in this study considering different laboratories using different thromboplastin reagents were utilized.…”
Section: Discussionmentioning
confidence: 95%
“…Canine specific monoclonal antibodies (mAbs) were raised in mice by immunisation with recombinant canine FVIIa (rcFVIIa) (Knudsen et al, 2010) using standard procedures (Appendix A supplementary material). …”
Section: Methodsmentioning
confidence: 99%
“…Sample FVII:Ag was calculated using SOFTmax Pro (Molecular Devices) by comparing OD 450nm signals from a seven point second order standard curve created with 0.3–30 nmol/L recombinant canine FVII. The stock concentration of the reference standard was determined using a micro-volume spectrophotometer (Knudsen et al, 2010). …”
Section: Methodsmentioning
confidence: 99%